Changes in enzyme activity and microbial community of rhizosphere soil under continuously monocultured Passiflora edulis treatment - Weiwei Lin; Zhihan Chen; Zhaowei Li; Wenxiong Lin (PLoS ONE, 2025)
In response to the severe continuous cropping obstacles encountered during the cultivation of passion fruit, which leads to significant declines in yield and quality, as well as rampant pests and diseases, it is particularly important to explore strategies for mitigating these obstacles. The present study used the rhizosphere soil samples from one-year-old (FY, first-year cropping) and two-year-old (SY, second-year cropping) “Golden Passion Fruit” plants, along with soil from uncropped land (CK) as a control and the techniques such as high-throughput sequencing, qRT-PCR, and HPLC-MS to analyze the main physicochemical properties, phenolic acid content, and microbial community changes in the rhizosphere soil of passion fruit under different continuous cropping durations, the results indicated that the contents of total nitrogen, total phosphorus, available nitrogen, available phosphorus, available potassium, and organic matter in FY soil were significantly higher than those in SY soil, and the pH value of the FY soil was also significantly higher than that of SY soil. Additionally, compared with FY soil, the activities of polyphenol oxidase, peroxidase, urease, and invertase in SY soil were significantly reduced by 18.0%, 43.6%, 19.8%, and 45.5%, respectively. HPLC analysis revealed that the concentrations of syringic acid, vanillin, benzoic acid, and ferulic acid in the SY soil were significantly increased by 18.0%, 21.9%, 24.4%, and 21.1%, respectively, compared to those in the FY soil. qRT-PCR analysis showed that as the duration of continuous cropping increased, the total number of bacteria in the rhizosphere soil of passion fruit decreased by 9.37%, while the total number of fungi increased by 57.8%. High-throughput sequencing results demonstrated that at the genus level, the relative abundances of Acidothermus, Acidibacter, Bacillus, and Acidobacterium were significantly increased by38.0%, 56.3%, 34.3%, 77.3%. whereas the relative abundances of Rhizomicrobium, Nitrospira, Burkholderia, Sphingomonas, Gemmatimonas, Streptomyces, and Nocardioides were significantly lower 45.2%,59.3%,50.6%,89.1%,74.5%,82.7% in the SY soil, relative to those in the FY soil. In summary, as the duration of continuous cropping increases, the soil fertility, enzyme activity, pH value, and beneficial microbial content in the rhizosphere of passion fruit decrease significantly, while the contents of phenolic acids and pathogenic microorganisms increase significantly. The findings of this study provide a theoretical basis for further elucidating the formation mechanism and mitigation strategies of continuous cropping obstacles in passion fruit.